PERAN AESTHETIC EXPERENTIAL QUALITIES DAN PERCEIVED VALUE UNTUK KEPUASAN DAN LOYALITAS PENGUNJUNG WISATA BAHARI DI PROVINSI LAMPUNG - Nurul Husna; Dian Novita (Universitas Merdeka Malang, 2020)
Tourism is important sector of economy in Indonesia, because including the top 10 contributors of foreign exchange. Indonesia’s marine tourism is one of Indonesia’s charm that attracts much attention for Indonesian visitors and also International visitors. The purpose of this research is to find out how the aesthetic experiential qualities and perceived value by tourist visitors in influencing the satisfaction and loyalty of marine tourism visitors in Lampung Province. Sample of this research is 100 visitors Pahawang Island in Lampung Province. This research use data analysis method uses smartPLS. The result of this research shows that aesthetic experiential qualities and perceived value have effect on visitor’s satisfaction, and visitor’s satisfaction has effect on visitor’s loyalty.